Laser-patterned carbon coatings on flexible and optically transparent plastic substrates for advanced biomedical sensing and implant applications. Issue 8 (13th January 2022) - Joshi, Pratik; Riley, Parand R.; Denning, Warren; Shukla, Shubhangi; Khosla, Nayna; Narayan, Jagdish; Narayan, Roger
Abstract : Plasma and laser-based processing for tailoring DLC thin film properties for state-of-the-art wearable sensing applications. Abstract : Medical grade polyethylene-based skeletal implants exhibit osteo-disintegration, erosion, and modest hemocompatibility. Herein, we report on the fabrication of highly adherent undoped and Si-containing DLC (Si-DLC) coatings for biomedical implant applications by utilizing plasma and laser-based processing techniques on thermally sensitive polyethylene (PE) substrates. Scratch testing reveals a strong interfacial shear strength of 620 MPa for DLC coatings deposited on PE. A contact stress of ∼32 MPa induced cracking of the DLC thin film. The Si-DLC films demonstrated a higher critical failure load and less cracking compared to undoped DLC films. The contact angle for PE increased from 90° to 110° when it was coated with the Si-DLC thin film. A high optical bandgap of 2.5 eV was calculated for the 21 at% Si-DLC thin films. Pulsed laser annealing (PLA) of Si-DLC films at 0.3 J cm −2 increased the amount of sp 2 bonded carbon, resulting in an improvement in lubricity, hydrophobicity, and electrical conductivity properties. In addition, the laser patterned pristine DLC films showed the formation of reduced graphene oxide, which possessed sizeable properties for wearable electronics and biosensing applications ( R s = 0.6 kΩ □ −1 ). This study indicates that PLA is a useful technique for modifying the properties of DLC thin films on flexible polymeric substrates for state-of-the-art biomedical and electronic sensing applications.